Native Americans and the Christian Right : The Gendered Politics of Unlikely Alliances - Smith, Andrea, 1966- (Book collections on Project MUSE., 2008)
Argues that previous accounts of religious and political activism in the Native American community fail to account for the variety of positions held by this community.